PENGARUH TEKNIK MARMET TERHADAP KELANCARAN PENGELUARAN ASI PADA IBU POST PARTUM DI KOTA PALEMBANG - Murdiningsih .; Siti Hindun; Heni Sumastri; Rohaya . (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2021)
Data of Public Health Service in Palembang revealed that the coverage of giving Exclusive breastmilk in Palembang in the year of 2015 was 72,91%. In plaju District, the coverage of exclusive breastmilk production was 77%. This coverage was still below the target that was 80%. The amount of breastmilk production in the first day after the childbirth was very small. It was caushed by the lack of two vital hormones in milk production, prolactine hormone and oxytocin hormone stimulus. This problem could be overcome by using the Marmet Technique. The aim of this research was to figure out the effect of the Marmet Technique towards the breast milk expression for the mother postpartum. The research designs used in this research were Pre-Experiment and One Group Pre-test Post-test. To collect the data, purposive sampling techniques was employed with the total of sample 30 respondents. Based on the result of univariate analysis, before the Marmet Technique in the smoothness of breastmilk expression was given, the result was 19 respondents (63,3%). On the other hand, after the treatment was applied, there are 15 respondents (50%). As for thes result of bivariate analysis, ρ value: 0,000 whilst (<α=0,05) which meant that the result was significant. It could be smmarised that the Marmet Technique influenced the smoothness of breast milk expression. Keyword: Marmet Technique, the smoothness of breast milk expression